Reduction in the rate of postoperative delirium by switching from famotidine to omeprazole in Japanese hepatectomized recipients - Miho Yamasaki; Yusa Fukuda; Aika Tanimoto; Miko Narahara; Yumi Kawaguchi; Hiromi Ushiroda; Saburo Fukuda; Teruo Murakami; Yorinobu Maeda (BMC, 2019)
Abstract Background Hepatectomy is a highly invasive procedure with a high probability of postoperative delirium. Treatment with antiulcer drugs is indispensable after hepatectomy for anastomotic ulcer management. The clinical pathway for hepatectomy was reviewed and the antiulcer drug used was switched from famotidine, a H2-receptor antagonist, to omeprazole, a proton pump inhibitor, owing to the pharmacist's intervention. Methods Hepatectomized recipients over 65 years of age, except in the cases of laparoscopic surgery and intensive care unit entry, were treated with famotidine injections (10 patients) or omeprazole injections (11 patients), and the incidence rates and severity of delirium were compared between the famotidine and omeprazole groups. The delirium after hepatectomy was assessed using the Japanese version of the NEECHAM confusion scale. Results The incidence rates of delirium were 90% in the famotidine group and 27.3% in the omeprazole group. Four out of 9 recipients in the famotidine group were injected with haloperidol to treat for delirium, but no recipients needed this treatment in the omeprazole group. Conclusions Compared with famotidine, the use of omeprazole was found to be effective in reducing the incidence rate and severity of postoperative delirium in patients undergoing hepatectomy. Pharmacists should actively strive to mitigate the risks of delirium.